Correlation between optic nerve sheath diameter and Rotterdam computed tomography scoring in traumatic brain injury - Mahima Kale R; Rajeswari G; Anil Kumar Sakalecha; Varshitha GR; Kalathuru Uhasai; Shantala Sawkar (Asian Journal of Medical Sciences, 2023)
Background: In India and other developing nations, traumatic brain injuries (TBIs) are main cause of disability, socioeconomic loss, morbidity, and mortality. In patients with TBI, Rotterdam CT score (RCTS) and diameter of optic nerve sheath (ONSD) have both been reliable independent predictors of prognosis. ONSD measurement has become a substitute non-invasive technique for keeping track of intracranial pressure (ICP). Aims and Objectives: The aims of this study were to study correlation between ONSD and RCTS in predicting outcome and prognosis in patients with traumatic brain injury. Materials and Methods: Total 90 patients with TBI were included in study. All patients meeting inclusion criteria were included and CT scan was performed. RTCS was done based, on which patients were divided into two groups (mild and severe head injury). According to standard protocol, ONSD was measured. Results: Among 90 cases included that most common cause of injury was motor vehicle accident (72.2%). Mean ONSD in the present study was 4.37±0.84 mm. About 57 (63.3%) patients had RCTS score of 1, 2, and 3 (mild head injury) and 33 (36.7%) had RCTS score of 4, 5, and 6 (severe head injury). Cutoff value of ONSD for predicting severity of TBI derived from receiver operating characteristic curve was >4.4 mm. There is a positive correlation between ONSD and RCTS. Conclusion: CT ONSD is a useful radiological tool to identify elevated ICP and it should be noted in every CT report in TBI cases.